2018
DOI: 10.1021/acsomega.7b01472
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin and GM1 Influence Huntingtin Binding to, Disruption of, and Aggregation on Lipid Membranes

Abstract: Huntington disease (HD) is an inherited neurodegenerative disease caused by the expansion beyond a critical threshold of a polyglutamine (polyQ) tract near the N-terminus of the huntingtin (htt) protein. Expanded polyQ promotes the formation of a variety of oligomeric and fibrillar aggregates of htt that accumulate into the hallmark proteinaceous inclusion bodies associated with HD. htt is also highly associated with numerous cellular and subcellular membranes that contain a variety of lipids. As lipid homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 93 publications
1
37
0
Order By: Relevance
“…The underlying mechanisms remain to be determined, although it was found that GM1 treatment increases phosphorylation of mHTT at Ser13 and Ser16, a crucial post-translational modification associated with a reduction in mHTT aggregation and toxicity ( Gu et al, 2009 ). Furthermore, a recent study showed that the presence of GM1 in artificial membranes made with total brain lipid extract dramatically decreases membrane insertion of exon 1 mHTT, and slows down the appearance of mHTT oligomers formed on membranes ( Chaibva et al, 2018 ). Whether administration of GM1 can affect the kinetics of mHTT aggregation or the aggregate species that are formed in vivo remains unknown.…”
Section: Gangliosides In Neurological and Neurodegenerative Conditionmentioning
confidence: 99%
“…The underlying mechanisms remain to be determined, although it was found that GM1 treatment increases phosphorylation of mHTT at Ser13 and Ser16, a crucial post-translational modification associated with a reduction in mHTT aggregation and toxicity ( Gu et al, 2009 ). Furthermore, a recent study showed that the presence of GM1 in artificial membranes made with total brain lipid extract dramatically decreases membrane insertion of exon 1 mHTT, and slows down the appearance of mHTT oligomers formed on membranes ( Chaibva et al, 2018 ). Whether administration of GM1 can affect the kinetics of mHTT aggregation or the aggregate species that are formed in vivo remains unknown.…”
Section: Gangliosides In Neurological and Neurodegenerative Conditionmentioning
confidence: 99%
“…The subcellular location of htt, necessitates its interaction with the lipid membrane bilayer and is mediated by posttranslational modifications of Nt17 residues . Additionally, the interaction of Nt17 with the lipid membrane bilayer has been shown to be an important factor in protein aggregation in HD where Nt17 can participate in lipid‐binding as well as protein‐protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Such lipid interactions have been shown to be modulators of aggregation and fibril formation also for α -synuclein (57,62,64), islet amyloid polypeptide (9) and βamyloid (58,84). Within these studies the detailed membrane composition including the resulting physico-chemical properties such as negative charge density, fluidity, saturation, curvature or interactions with specific lipids all play important roles in the aggregation process (9,39,56,76,85). Thereby, the membrane interactions of polyQ flanking regions and their modulation by posttranslational modifications provides a possible therapeutic intervention site which has to our knowledge not been explored in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…Another huntingtin domain mediating membrane interactions has been identified within residues 171-371, a region bearing an overall high cationic character (10). Furthermore, biochemical and cell biological assays demonstrate the potential role of these anchoring domains in disease development (10,21,41,42,55,56).…”
mentioning
confidence: 99%
See 1 more Smart Citation